Multicentre evaluation of anxiety and mood among collegiate student athletes with concussion. Issue 1 (3rd February 2023) - Lumba-Brown, Angela; Teramoto, Masaru; Zhang, Rachel; Aukerman, Doug F; Bohr, Adam D; Harmon, Kimberly; Petron, David J; Romano, Russ; Poddar, Sourav K; Ghajar, Jamshid
Abstract : Objectives: Mental health problems are a premorbid and postinjury concern among college student athletes. Clinical phenotypes of anxiety and mood disruption are prevalent following mild traumatic brain injury, including concussion, a common sports injury. This work examined whether concussed student athletes with a history of mental health problems and higher symptoms of anxiety and mood disruption at baseline were more likely to have higher postinjury reports of mood and anxiety as well as prolonged resolution of postconcussive symptoms to near-baseline measures. Methods: This was a retrospective cohort study of a multi-institutional database of standardised baseline and postinjury assessments among college student athletes. Anxiety/mood evaluation data among varsity college athletes from four institutions over 1 year were measured and compared at baseline and postconcussion recovery using descriptive statistics and multilevel/mixed-effects analysis. Results: Data from 2248 student athletes were analysed, with 40.6% reporting at least one symptom of anxiety and/or mood disruption at baseline. Of the 150 distinct concussions, 94.7% reported symptoms of anxiety/mood disruption during recovery (recovery time=0–96 days). Higher anxiety/mood scores at baseline were significantly associated with higher scores following concussion (p<0.001). Recovery trajectories of anxiety/mood scores showed different patterns by sex and prolonged recovery. Conclusion: Symptoms of anxiety and mood disruption are common at baseline among college student athletes. These students are at higher risk for symptomatology following injury, representing a screening cohort that may benefit from early counselling. Almost all student athletes will experience symptoms of anxiety and/or mood disruption following concussion.